The Effect of Oral Nutritional Supplements on Nutritional Risk in Post-Discharge Patients After Colorectal Cancer Surgery: A Randomized Clinical Trial - Bhoi, Suraj Kumar; Saxena, Anuj; Panda, Kedarnath (Student's Journal of Health Research Africa, 2024)
Background: Colorectal cancer surgery often leaves patients at nutritional risk, impacting their recovery and quality of life. Oral nutritional supplements (ONS) may offer benefits in improving nutritional status and overall health outcomes in these patients. This study aimed to evaluate the impact of ONS on post-discharge patients at nutritional risk following colorectal cancer surgery. Methods: A randomized clinical trial was conducted, including a total of 160 patients with a Nutritional Risk Screening 2002 (NRS 2002) score of 3 or higher were randomized into the ONS group (n=80) and control group (n=80). The ONS group received dietary advice and Nutren® Optimum for three months, while the control group received only dietary advice. Nutritional outcomes, readmission rates, chemotherapy tolerance, and quality of life (QoL) were assessed. Results: Out of the 160 enrolled patients, 148 completed the study. The ONS group showed significant improvements in weight (63.5 ± 10.2 kg vs. 61.0 ± 9.8 kg, p=0.048), BMI (23.4 ± 3.2 kg/m² vs. 22.0 ± 3.4 kg/m², p=0.018), serum albumin (3.8 ± 0.4 g/dL vs. 3.5 ± 0.5 g/dL, p<0.001), and hemoglobin levels (12.5 ± 1.1 g/dL vs. 11.8 ± 1.3 g/dL, p=0.002) compared to the control group. The ONS group also had lower readmission rates (10.8% vs. 24.3%, p=0.034) and higher chemotherapy tolerance (83.8% vs. 70.3%, p=0.047). QoL scores were significantly better in the ONS group across multiple domains. Conclusion: The use of ONS significantly improves nutritional status, reduces readmission rates, enhances chemotherapy tolerance, and improves the quality of life in post-discharge patients following colorectal cancer surgery. Recommendations: Incorporating ONS into the post-discharge care plan for colorectal cancer patients at nutritional risk is recommended to enhance recovery and improve health outcomes.